Saberes do trabalho na carpintaria naval artesanal no distrito de Carapajó – município de Cametá-PA - PANTOJA, Pedro Ladinilson do Rosário (Universidade Federal do Pará, 2017)
This paper investigates the issue of working knowledge within the productive activity of small-scale shipbuilding in the town of Carapajó, Cametá, Pará State, based on a study of the ethical, political, technical, pedagogical and organizational, related to the construction of the Plant hydroelectric Tucuruí, Pará. The main hypothesis of this work is that the dynamics of organization of knowledge work is characterized as an ongoing process of construction and reconstruction of social knowledge, which are articulated in turn, with the professional experiences gained through work. In its theoretical basis, this research makes use of historical and dialectical materialism and takes the contradiction, denial of denial and alienation as categories of analysis in social relations as well as historical, which produce the existence of the craftsmen of shipbuilding. Through this study, it was found the existence of technical knowledge, typological order in terms of vessel, based on the economic and social needs of the region, and also identified a set of political knowledge, of constative character, concerning the existence of a job reduction process and a class consciousness itself, which recognizes the suffering at work. However, there is no action on organizing workers in terms of counter-hegemony, due to lack of class consciousness among these workers. To that end, it was understood that there is still a knowledge of identity transformation among craftsmen, and it is driven much more by capitalism than by the political organization of these workers. Soon, the pedagogical knowledge that result from production-training process, as an educational principle, are also built knowledge about the organization of work, which shows an integral formation of the subject for professional practice.